Pile-Spacing Calculation of Anti-Slide Pile Based on Soil Arching Effect - Guangfu Chen; Liangchao Zou; Qing Wang; Guodong Zhang (Advances in Civil Engineering)
Anti-slide pile is one of the most frequently used measures in landslide control globally. Pile-spacing has always been determined by the load capacity of single piles or according to engineering empirical experience. Many engineering practices and laboratory experiments show that the soil arching effect exists in landslide control with anti-slide piles. In this study, we aim to calculate pile-spacing in terms of the soil arching effect. We investigated the pile-soil interaction mechanism and propose that, at the limit, the pile-back soil arch resists landslide thrust only. According to Mohr–Coulomb strength theory and limit equilibrium theories, we derived a new pile-spacing calculation equation. We verified the derived pile-spacing calculation equation with real projects. The calculated results are similar to those of practical engineering designs, in which the difference is within 10%. The equation can be used in anti-slide pile preliminary design. This study can be a reference for pile-spacing calculation based on the soil arching effect.